2020
DOI: 10.3390/ma13163484
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive Affordable Cementitious Composite with High Mechanical and Microstructural Performances by Hybrid CNT/GNP

Abstract: In this paper a hybrid combination of carbon nanotubes (CNTs) and graphene nanoplatelets (GNPs) was used for developing cementitious self-sensing composite with high mechanical, microstructural and durability performances. The mixture of these two nanoparticles with different 1D and 2D geometrical shapes can reduce the percolation threshold to a certain amount which can avoid agglomeration formation and also reinforce the microstructure due to percolation and electron quantum tunneling amplification. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 49 publications
5
46
1
Order By: Relevance
“…The FCR amounts did not reach zero at the end of each loading cycle and a negligible amount of FCR remained after unloading, which is consistent with the strain remaining at the end of each loading cycle, and was increased by increasing load cycles. These remaining amounts were lower than those of previous studies [5] due to the compaction fabrication methods.…”
Section: Piezoresistivity Investigationscontrasting
confidence: 69%
See 3 more Smart Citations
“…The FCR amounts did not reach zero at the end of each loading cycle and a negligible amount of FCR remained after unloading, which is consistent with the strain remaining at the end of each loading cycle, and was increased by increasing load cycles. These remaining amounts were lower than those of previous studies [5] due to the compaction fabrication methods.…”
Section: Piezoresistivity Investigationscontrasting
confidence: 69%
“…According to these results, the percolation threshold for this type of reinforced CSS could be around 0.24% due to the insignificant effect of CNM on reducing electrical resistivity in increments beyond 0.24%. By comparing the results with other studies that used similar types of sand, cement, dispersion method, and CNM, in order to investigate piezoresistivity and electrical conductivity of cementitious mortar (W/C = 0.5) [ 5 , 28 ], it can be observed that decreasing the cement concentration in CNM-reinforced cementitious composite led to the reduction in electrical resistivity. Comparing these results also showed that the use of a compaction fabrication method can reduce the electrical resistivity by up to 80%.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…They may also yield better mechanical capacity [ 23 ], decreased costs, and reduced environmental and health impacts from the reduction of the required amount of filler. Literature reports studies on hybrid doping, including carbon black-graphene [ 24 ], carbon nanotubes-graphene nanoplatelets [ 25 ], carbon nanotubes-nano carbon black [ 26 ], carbon nanotubes-carbon fibers [ 27 ], carbon black-conductive rubber fibers [ 28 ], carbon black-polypropylene fibers [ 29 ], steel fibers-carbon nanotubes [ 30 ], carbon black-block co-polymer (SEBS) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%